2023
DOI: 10.1007/s12626-023-00133-3
|View full text |Cite
|
Sign up to set email alerts
|

On the Work Autonomy Supported by Information and Communication Technology A Case Study of Work from Home in Japan before the COVID-19 Epidemic

Abstract: Telecommuting increased during the COVID-19 pandemic. To make telecommuting the “new normal,” it is essential to not only change the legal system and employment contracts but also reform organizational processes. Prior research has demonstrated a positive correlation between telecommuting and perceived autonomy using questionnaire surveys, but the lack of a widely accepted measurement scale to capture the reality of telecommuting has hindered the capacity to understand its current status. In this study, we con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…• Organizational issues, including work performance (Ficapal-Cusí et al 2023;Mirowska and Bakici 2023); employee-supervisor relationship (Park et al 2023); issues with communication, trust, control, and productivity (Fontaneda et al 2023), especially in the context of banking institutions (Meyer et al 2022); the need to reform organizational processes (Yanagihara and Koga 2023); focus more on cooperation than subordination and increasing autonomy (Junça Silva and Coelho 2023;Stanciu et al 2023); need to reform organizational culture to fit the telework model while focusing on trust equality and confidentiality (Junça Silva and Coelho 2023;Mirowska and Bakici 2023;Bayazitova et al 2023); and re-structure organizational benefits policy to fit the telework model (Brandão and Ramos 2023;Fontaneda et al 2023), as well as utilize flexible working hours (Dimian et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…• Organizational issues, including work performance (Ficapal-Cusí et al 2023;Mirowska and Bakici 2023); employee-supervisor relationship (Park et al 2023); issues with communication, trust, control, and productivity (Fontaneda et al 2023), especially in the context of banking institutions (Meyer et al 2022); the need to reform organizational processes (Yanagihara and Koga 2023); focus more on cooperation than subordination and increasing autonomy (Junça Silva and Coelho 2023;Stanciu et al 2023); need to reform organizational culture to fit the telework model while focusing on trust equality and confidentiality (Junça Silva and Coelho 2023;Mirowska and Bakici 2023;Bayazitova et al 2023); and re-structure organizational benefits policy to fit the telework model (Brandão and Ramos 2023;Fontaneda et al 2023), as well as utilize flexible working hours (Dimian et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The distance from the workplace induced in the context of telework during the COVID-19 pandemic generated new dilemmas in work performance (Ficapal-Cusí et al 2023). Moreover, it has been suggested that "to make telecommuting the 'new normal', it is essential to not only change the legal system and employment contracts but also reform organizational processes" (Yanagihara and Koga 2023). Following the advent of the increase in telework adoption after the COVID-19 pandemic, teleworking has begun to dramatically change the work dynamics for all stakeholders, and the relations between employer and employee are "expected to become based more and more on cooperation and less on subordination", utilizing the telework model (Stanciu et al 2023).…”
Section: Related Evidence From Recent Literature On Telework In the C...mentioning
confidence: 99%
See 1 more Smart Citation